1990
DOI: 10.1080/00268949008042204
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Derivative Films for Liquid Crystal Alignment

Abstract: We studied the alignment of liquid crystal molecules on rubbed, thin polymer films of polystrene and its derivatives. Liquid crystal molecules were aligned perpendicular to the rubbing direction, although the polymer main chains of rubbed films were oriented along the rubbing direction. The alignment of the liquid crystal depended on the choice of side phenyl groups of polystyrene derivatives, and the pretilt angle varied with the type and the position of the substituents that were introduced into the side phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
16
1
Order By: Relevance
“…These LC alignment results are similar to those observed for rubbed PS films [30,31], for which the director of the LC alignment always coincides with the orientation direction of the generated microgrooves. However, the observed LC alignment of our study is a significant departure to that reported previously for rubbed P4VP films [32], when the LC alignment was found to be perpendicular to the rubbing direction.…”
Section: Alignment and Anchoring Energy Of Lcscontrasting
confidence: 79%
See 2 more Smart Citations
“…These LC alignment results are similar to those observed for rubbed PS films [30,31], for which the director of the LC alignment always coincides with the orientation direction of the generated microgrooves. However, the observed LC alignment of our study is a significant departure to that reported previously for rubbed P4VP films [32], when the LC alignment was found to be perpendicular to the rubbing direction.…”
Section: Alignment and Anchoring Energy Of Lcscontrasting
confidence: 79%
“…Poly(2-vinylpyridine) (P2VP) is an isomeric polymer of P4VP, but in contrast its rubbed films have been reported to induce LC alignment with zero pre-tilt parallel to the rubbing direction [32]. However, despite their interesting reported LC alignment behavior, the films of these polymers have rarely been studied.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rubbing method involves rubbing the polymer-coated substrate surface against a cloth, and despite being a somewhat antiquated technique, the detailed mechanism of LC alignment by the rubbing process has yet to be reported. Recently, the alignment mechanism has been reported to be the result of geometric effects of structures such as grooves [1][2][3][4][5] or a uniaxis expanding effect of the polymer film [6][7][8][9][10]. Although uniform LC alignment can be readily achieved by the rubbing method, the method does present a number of problems, including the generation of dust and static electricity.…”
Section: Introductionmentioning
confidence: 99%
“…Papers on polymer buffing predicated that the oriented polymer chains induced LC alignments by the orientational epitaxy. [1][2][3][4] On the other hand, a photo-alignment method has attracted a good deal of theoretical and experimental attentions. This is not only due to the improvement of the production yield of LCDs, but also due to the fundamentals of LC alignment physics.…”
Section: Introductionmentioning
confidence: 99%